2017
DOI: 10.1038/ncomms14680
|View full text |Cite
|
Sign up to set email alerts
|

T cell costimulation blockade blunts pressure overload-induced heart failure

Abstract: Heart failure (HF) is a leading cause of mortality. Inflammation is implicated in HF, yet clinical trials targeting pro-inflammatory cytokines in HF were unsuccessful, possibly due to redundant functions of individual cytokines. Searching for better cardiac inflammation targets, here we link T cells with HF development in a mouse model of pathological cardiac hypertrophy and in human HF patients. T cell costimulation blockade, through FDA-approved rheumatoid arthritis drug abatacept, leads to highly significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
139
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 157 publications
(162 citation statements)
references
References 67 publications
14
139
1
4
Order By: Relevance
“…Yet many HF patients display HFpEF. We have recently shown that, surprisingly, in cardiac biopsies of both patients with HFrEF or HFpEF, T cell presence in the ailing myocardium appears to correlate with the degree of fibrosis, and thus with disease severity …”
Section: T Cell Involvement In Hfmentioning
confidence: 99%
See 4 more Smart Citations
“…Yet many HF patients display HFpEF. We have recently shown that, surprisingly, in cardiac biopsies of both patients with HFrEF or HFpEF, T cell presence in the ailing myocardium appears to correlate with the degree of fibrosis, and thus with disease severity …”
Section: T Cell Involvement In Hfmentioning
confidence: 99%
“…The correlation between inflammation and cardiac dysfunction can be elegantly demonstrated in preclinical mouse models, such as the transverse aortic constriction (TAC) model, the gold‐standard preclinical model for HF . In order to visualize this correlation in an intuitive manner, we used recently generated and published data for the expression of cytokines in the myocardium of TAC‐operated mice at different time points of the disease. We performed a meta‐analysis, plotting an index of heart dysfunction (loss in percent fractional shortening, i.e., the decrease in pumping volume of the ventricle, measured by echocardiography; details on calculations shown in the figure legend) against an arbitrary index of inflammation (i.e., the ratio of cardiac mRNA expression of the proinflammatory cytokine IL‐6 to the anti‐inflammatory cytokine IL‐10) (Figure A).…”
Section: The Cytokine Hypothesismentioning
confidence: 99%
See 3 more Smart Citations